Effectiveness of Google Sites–Assisted Problem-Based Learning on High School Students' Analytical Skills in Lithosphere Learning - Dian Tri Cahyani; Yuswanti Ariani Wirahayu; Maria Cicilia Tri Palupi (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examined the effectiveness of Problem-Based Learning (PBL) assisted by Google Sites in improving students' analytical thinking in lithosphere topics. A quasi-experimental nonequivalent control group design involved 68 tenth-grade students, divided into an experimental (PBL and Google Sites) and a control (conventional instruction) group. Analytical skills were measured with a validated essay test targeting the indicators of differentiating, organizing, and attributing. Data were analyzed with the Mann–Whitney U test due to non-normality. Results showed a significant difference (p < 0.05), with the experimental group achieving higher mean scores and a large effect size (r = 0.79). The findings indicate that integrating PBL with a web platform effectively enhances analytical competence in geography learning. Practical implications suggest that teachers can use Google Sites to structure problem scenarios, learning tasks, worksheets, and assessments. Limitations include single-school sampling and short treatment duration; future research should apply N-gain analysis, test other topics, and compare platforms.